(untitled) (MARSEGU : Jurnal Sains dan Teknologi, 2025)
This research aims to determine the housing system and equipment for pig farming in Suli Country and to determine the productivity of pig farming in Suli Country. The research was carried out in Suli Country, using survey methods and direct observation in the field. The number of respondents was 44 breeders. Data collection was carried out through direct interviews, observation and documentation. The data obtained was grouped and tabulated, then used quantitative analysis with a descriptive statistical approach. The research results show that the majority of breeders in Suli Country (72.27%) use single cages with integrated eating and drinking equipment. 75% of farmers have separation pens, but do not provide special feeding areas for piglets, and use heat lamps for heating. A comfortable housing system supports productivity with an average litter size of 6 ± 2.30 birds, birth weight of 1.42 ± 0.31 kg, and weaning weight of 7.10 ± 0.79 kg. The piglet mortality rate is low (1.36%) thanks to proper hygiene and heating.